carlenstar281 2 years ago help me please Algebra 1

1. ghazi

2$(-2)^{-3*24}=(-2)^{72}$

2. whpalmer4

I think that should be $(-m)^{-3}n$ Yes?

3. ghazi

what exactly is your question, what are you supposed to find?

4. whpalmer4

First thing to remember is that $x^{-m} = \frac{1}{x^m}$If we rewrite the expression in that fashion, we get $\frac{n}{(-m)^3} = \frac{-24}{(-2)^3}$Can you evaluate that?

5. whpalmer4

$(-2)^3 = (-2)*(-2)*(-2)$

6. ghazi

well no

7. carlenstar281

its negative though right?

8. carlenstar281

its -3 right?

9. whpalmer4

@ghazi what do you mean, "well no"?

10. carlenstar281

he means its not -4

11. whpalmer4

Did someone say it was? $\frac{-24}{(-2)*(-2)*(-2)}$What does the expression on the bottom equal?

12. ghazi

its not -4 , its 4 ,if the explanation of @whpalmer4 is true and second i am not sure if that explanation is true, it would be great if you could take snapshot and post it here :D @carlenstar281

13. carlenstar281

I cant but thank you for helping me :)

14. ghazi

:) YW

15. whpalmer4

Yes, all of my statements are true and correct. The answer is not 4.

16. carlenstar281

are you sure i get 4?

17. whpalmer4

What is -2 * -2 * -2?

18. ghazi

$\frac{ -24 }{ -2*-2*-2 }=\frac{ -24 }{ -8 }---> -A*-A*-A=-A$

19. ghazi

and $\frac{ -24 }{ -8 }=\frac{ 24 }{ 8 }=3$ LOL

20. ghazi

that was the silliest mistake i've ever done

21. carlenstar281

sorry computer froze haha its okay i did that to still thanks for helping!

22. ghazi

np :)

23. carlenstar281

also thank you to @whpalmer4 as well haha

24. whpalmer4

Another way of looking at this is $\frac{-24}{(-1*2)^3} = \frac{-24}{(-1)^3*2^3}$$$-1^n = -1, n$$ odd so we have $\frac{-24}{-1*2^3} = \frac{-24}{-8} = 3$

25. whpalmer4

We can factor out that -1 because $(ab)^n = a^nb^n$